A nomogram to predict survival probability of gastric cancer patients undergoing radical surgery and adjuvant chemotherapy - Ma, Ling; Chen, Guosheng; Wang, Deqiang; Zhang, Kai; Zhao, Fengjiao; Tang, Jie; Zhao, Jianyi; Røe, Oluf Dimitri; He, Shaohua; Liao, Dongcheng; Gu, Yanhong; Tao, Min; et al. (Frontiers in Oncology, 2022)
Gastric cancer (GC) is the third-leading cause of cancer mortality worldwide. The aim of this study was to develop a nomogram that estimates 1-year, 3-year, and 5-year survival probability of GC patients after D2 gastrectomy combined with adjuvant chemotherapy. The results showed that median age is 58 (range: 18-85) years in the training cohort and 59 (range: 32-85) years in the validation cohort. On multivariate analysis, four factors were found to be significantly associated with worse overall survival (OS): late TNM stage, positive resection margin, preoperative carcinoembryonic antigen (CEA) level, and single chemotherapy regimens compared with multiple chemotherapy regimens. All of these findings were validated in the validation cohort. Furthermore, the four factors were included in the final nomogram for the prediction of 1-year, 3-year, and 5-year survival probability, with accurate calibration and reasonable discrimination (C-index = 0.676 for training cohort, and C-index = 0.664 for validation cohort). The AUC values analyzed by the ROC analysis demonstrated a good predictive accuracy of the nomogram for OS (1-year, 3-year, and 5-year OS were 94.43%, 77.42%, and 73.03% in the training cohort, respectively; 96.95%, 81.54%, and 73.41% in the validation cohort, respectively). In conclusion, the proposed nomogram may be used to objectively and accurately predict survival probability of GC patients in a multi-institutional clinical setting.